Avaliação comparativa do potencial osteocondutor de quatro diferentes substitutos ósseos em defeitos críticos em calvárias de coelhos - Grossi-Oliveira, Gustavo Augusto [UNESP] (2016)
Objectives: To evaluate the osteoconductive potential of four biomaterials used in bone defects filling in rabbit’s calvaria. Methods: 24 male Albinus rabbits underwent to bone defect creation of 8 mm in diameter bilaterally in calvaria region. The groups were divided acordind to the bone substitute used to fill the calvaria defect: bovine hydroxyapatite - Bio-Oss ® (BIO), Lumina Bone Porus® (LBP) and Bonefill® (BFL), and an alloplastic material - Clonos® (CLN), and were submitted to euthanasia at 14 and 40 days after the surgery. The removed pieces were processed, histological slides were obtained and subjected to histological analysis; histometric analysis, through the measurement of newly formed bone area (NB) in the center of the defects; immunohistochemical analysis, by labelling the Runt-related transcription factor 2 (Runx2), vascular endothelial growth factor (VEGF) and osteocalcin (OC). Quantitative data were statistically analyzed (α = 0.05). Results: The CLN group showed greater AON in both periods analyzed in relation to the other groups (p <0.001, Tukey test). At 14 days, the AON showed greater values in BIO in relation with LBP and BFL groups, however , after 40 days, the LBP group surpassed the results of BIO (p <0.001, Tukey test). The immunostaining showed a decrease in Runx2 intensity in BIO after 40 days, while it increased for LBP (p <0.05, Tukey test). The CLN showed increased OC compared to the other groups in both periods analyzed (p <0.05, Tukey test). Conclusions: The CLN showed the best osteoconductive behavior in critical defects in rabbit’s calvaria.